Social determinants of tuberculosis - Lönnroth, Knut (Henry Stewart Talks, 2013)
History of TB trends in Europe, Association between TB and socioeconomic factors, Causal pathways, Direct risk factors for TB, The poverty-disease trap, Entry points for interventions on social determinants